A Dark Labyrinth of Risk Governance and Culture: A Sustainability of Higher Education in Indonesia - Nadeak, Bernadetha (Pedagogi: Jurnal Ilmu Pendidikan, 2026)
This research aims to highlight the complexities between regulations and practices in higher education, and to address the sustainability of organizations in Indonesia through risk governance and culture. Government regulations have transformed higher education governance, addressing changes that are not yet aligned with domestic and international competition. These drastic changes—what I call a dark labyrinth—have altered the strategies of higher education institutions for sustainability and regulatory compliance, resulting in stagnant or even declining growth. Therefore, my argument is that calculating risk governance and culture creates attitudes and behaviours that enable them to survive, adapt, and thrive in a complex environment. Using secondary sources, including books, articles, academic writings, and archival materials, this research explores the issues and generates an in-depth discussion. The findings of this study, specifically risk governance and culture, inform the process of shaping attitudes and behaviours among human resources in higher education. From these findings, I conclude that risk governance and culture are crucial determinants of compliance and play a vital role in shaping effective human resources management practices in higher education.